Examination and Prioritization of Wrestling Problems in Mazandaran Province from the Perspective of Coaches and Sports Managers and the Factors Influencing Them - Razaghi, Mostafa; Abdi, Ahmad (Journal of Foresight and Health Governance, 2025)
Wrestling, as one of Iran’s authentic and prestigious sports disciplines—especially in Mazandaran Province—faces numerous challenges that have constrained its development. This study was conducted with the aim of identifying and prioritizing the problems of wrestling in Mazandaran Province from the perspective of coaches and sports managers, to contribute to improving the status of this sport. The research employed a descriptive–survey design and was carried out in 2014. The statistical population included all wrestling coaches and managers in Mazandaran (estimated at 155 individuals), from which 120 participants were selected through multistage cluster sampling. Data collection was conducted using a researcher-made questionnaire with a 5-point Likert scale. The content validity of the instrument was confirmed, and its reliability was verified through Cronbach’s alpha coefficient (0.72). Data were analyzed using descriptive statistics and a one-sample t-test in SPSS version 20. The findings revealed that all 12 hypotheses were confirmed. The most significant problems included the lack of long-term planning (mean = 4.45), budget shortages (mean = 4.32), lack of well-equipped halls (mean = 4.33), and lack of job security for wrestlers (mean = 4.38). Economic factors such as the financial poverty of wrestlers (mean = 4.00) and insufficient income for coaches (mean = 3.75) were also identified as key challenges. Managerial and economic problems were determined to be the main barriers to the development of wrestling in Mazandaran. Increasing budget allocation, implementing comprehensive planning, and improving infrastructure could help address these challenges. The findings have practical implications for the Wrestling Federation and provincial sports boards.